Prospects of Machine Translation in the Chinese Context - Qian, Duoxiu (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractChina has been among the several leading countries in the research and applications of Machine Translation (MT) and Machine-aided Translation (MAT) ever since the 1950s. The first part of this paper is a historical sketch of MT and MAT in the Chinese context, highlighting some important stages in its development which have laid the foundation for later achievements. It is shown that the research of MT in this region is similar to that in other parts of the world, with the attention gradually turning to MAT. The second part deals with the state of the art of MT and MAT research and applications in Mainland China, Taiwan and Hong Kong, respectively. Then popular commercial software dedicated to the translation from Chinese into other foreign languages, and vice versa, are introduced, with an appraisal of both their merits and demerits. Finally, prospects of MT and MAT in the Chinese context is discussed. It is suggested that, for mutual benefits, MT and MAT research in the Chinese context should cooperate with the outside world more closely.